Mapping Drought Severity Based on Sentinel-2 Harmonized Data Using Google Earth Engine - Aldiansyah, Septianto; Ati, Amniar; Sudirman, Andi Sulia; Hasanah, Nur (Jurnal Penelitian Pendidikan Geografi, 2026)
Drought is a hydrometeorological disaster that significantly impacts ecosystems and the sustainability of land use, particularly in humid tropical regions that have long been considered relatively resilient. This study aims to analyze the level of drought in Konawe Selatan Regency using the 2024 Normalized Difference Drought Index (NDDI) with remote sensing via the Google Earth Engine platform. Inter-variable relationships were also analyzed using a statistical correlation approach to the Normalized Difference Vegetation Index (NDVI), Normalized Difference Water Index (NDWI), Land Surface Temperature (LST), and precipitation. The NDDI analysis indicates that moderate drought dominates up to 35.93% of the area, while low drought only covers 27.99%. The correlation between the NDDI and NDVI, NDWI, LST, and precipitation is relatively weak (R² <0.3), indicating that drought is not solely influenced by rainfall but is a multidimensional phenomenon. The results of this study can be used for drought mitigation and adaptation planning, water and land resource management, and as public information that can minimize the risk of drought impacts.